Analisis Faktor yang Berhubungan dengan Kelainan Siklus Menstruasi - Nurfazriah, Indah; Umaesaroh, Siti; Nurkhayati, Etty (Lembaga Pengembangan Kinerja Dosen, 2025)
Menstrual cycle abnormalities are one of the reproductive health problems that are commonly experienced by adolescent girls, especially in the early days after menarche. These disorders can affect quality of life, including discomfort during activities, risk of anemia, and potential fertility disorders. A preliminary study at SMA Negeri 4 Pandeglang showed that 7 out of 10 grade XI students experienced menstrual cycle abnormalities, while there was no special program related to reproductive health in schools. This study aims to analyze factors related to menstrual cycle abnormalities, namely stress levels, diet, and physical activity. The research design used was quantitative with a Cross Sectional approach, involving 70 respondents who were selected through the Purposive Sampling technique. Data collection was carried out through a structured questionnaire and analyzed using the Chi-Square statistical test. The results of the analysis showed that there was a significant relationship between stress (p=0.011), diet (p=0.021), and physical activity (p=0.015) with menstrual cycle abnormalities. These findings confirm the importance of educational interventions in the school setting to improve adolescents' understanding of reproductive health and encourage healthy lifestyles. This research is expected to be the basis for the development of more comprehensive promotive and preventive programs in supporting the welfare of adolescent girls.